A Biochemical Study Of High-Density Lipoprotein Cholesterol (Hdl-C) Changes In Middle Aged Common People With Different Lifestyle - Kanna, Suresh; Thamizhvanan, Premila; Bharathi, Jaya (Bangladesh Journal of Medical Science, 2017)
Background and rationale: HDL cholesterol is one of the 5 major groups of lipoproteins cholesterol, which enable lipids like cholesterol and TG to be transported within the water based blood stream. In healthy persons, about thirty percent of blood cholesterol is carried by HDL cholesterol. HDL-C is a potent predictor of coronary heart disease. Genetic as well as environmental factors including lifestyle factors play a role as determinants of its level in the blood. To examine the effects of certain lifestyle factors on serum level of high density lipoprotein cholesterol in young adult people HDL cholesterol seems to protect against CVD which increases the risk for heart disease. Subjects and methods: Three hundred and twenty five young adult subjects of both sexes aged 18-45 years asymptomatic for cardiovascular diseases were interviewed according to special questionnaire including information on lifestyle habits. Physical examination was done, height, body weight, and blood pressure measurements were performed. Blood analysis to determine the blood level of high density lipoprotein cholesterol was done after 12 hours fasting. Results and conclusion: Smoking and obesity were the most significant risk factors associated with a decreased level of high density lipoprotein cholesterol. The level of HDL-C was 50.5±11.5 mg/dl in smokers compared with 57.7±12.5 mg/dl in nonsmokers. Its level was 48.5 ±8.5 mg/dl in obese individuals compared to 57.5±11.7mg/dl in normal body weight subjects. Physical activity was not significantly associated with low level of HDL-C analysis, but it was found to be significantly associated with its level by the multiple regression analysis. High-density lipoprotein cholesterol level was a function of many factors, some of them were lifestyle related such as smoking, physical activity, and obesity. Therefore, efforts to encourage more physical activity, quitting smoking, consuming low fat diet, and keeping ideal body weight are recommended. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.289-294